COMPETITION LAW HARMONIZATION: WHAT ASEAN CAN LEARN FROM OTHERS? - Cenuk Sayekti (Refleksi Hukum: Jurnal Ilmu Hukum, 2020)
This paper examines the difficulties of competition law harmonisation in ASEAN. Harmonisation is believed as the main tool to help ASEAN from legal friction and tension when it engaged cross-border trade within its region. The benefits of harmonisation are expected to help the member states to avoid negative impact of anti-competitive conducts. Nevertheless, there is a concern arising from such integration of competition law: differences of treatment and dissonant of legal culture.